Low-income mothers' entry into postsecondary education during middle childhood: Effects on adolescents. (November 2019) - Martin, Anne; Gardner, Margo; Petitclerc, Amélie
Abstract: This study tests whether young adolescents' achievement and behavior are associated with their mother's entry into post-secondary education (PSE) during their middle childhood years. It also examines five family processes that may link maternal PSE to development in middle childhood (income, home learning environment, mother's educational expectations for child, maternal presence, and family affective climate). The sample selects low-income families from the National Longitudinal Survey of Youth of 1979. Propensity score weighting adjusts for mothers' self-selection into PSE. We find that adolescents whose mothers entered PSE in their middle childhood scored higher than their peers on math, but similarly on reading, behavior problems, delinquency, and substance use. There were no associations between mothers' PSE entry and the proposed mediators. Highlights: Mothers who return to school may boost child achievement but impair behavior. This study examined low-income families in a national, longitudinal sample using propensity score weighting. We examined adolescents whose mother entered post-secondary education in their middle childhood years They scored slightly higher than matched peers on math but the same on reading and behavior.